Fifty years after the 1967 crime commission report - Belknap, Joanne (Criminology & public policy, 2018)
In the 50 years since the U.S. President's Commission on Law Enforcement and Administration of Justice under President Johnson issued its report, feminist activism and both feminist and mainstream research have resulted in defining domestic violence (DV) as a social problem. This awareness of the seriousness and expansiveness of DV has spurred the development of unprecedented programs and policies. Although DV policing changes have been significant, so too have been the development of and changes in safehouses, no‐drop court policies, domestic violence courts, community‐coordinated responses, and batterer intervention programs. In this article, we review the nonpolice responses to DV cases and outcomes and provide recommendations. First, research and policies need to more regularly be aimed at addressing victims’ safety and their diverse needs and experiences. Second, assessments should include addressing the processing of these cases through the impact of responses by individual community and criminal legal system actors (e.g., victim advocates, police, prosecutors, and judges) to victims and offenders.